Perubahan Garis Pantai Pesisir Pulau Merah Banyuwangi dengan Citra Satelit Landsat 8 (2016 – 2025) - Bima Hanggara Nasrullah; Hendrata Wibisana; Bagas Aryaseta (Universitas Batanghari Jambi, 2026)
The study of shoreline changes at Pulau Merah Beach, Banyuwangi, highlights that this coastal tourism area is highly dynamic due to the influence of ocean waves, currents, and the deposition of sand and silt. Monitoring shoreline changes is essential to ensure that the tourism area remains safe, well-managed, and sustainable. This research aims to analyze the patterns of shoreline shifts from 2016 to 2025 and to distinguish between areas experiencing continuous erosion and those affected only occasionally. The data were obtained from Landsat 8 satellite imagery, which was processed using the Normalized Difference Water Index (NDWI). Ten observation lines (transects) with a spacing of approximately 100 meters were established, and annual shoreline shifts were measured using the Euclidean Distance method. The results show that some sections of the shoreline experience continuous erosion, particularly transects 1–4, which retreated almost every year by a considerable distance. Meanwhile, transects 6–9 were eroded only at certain times and later stabilized, while transects 5 and 10 displayed mixed patterns. This study demonstrates that transect analysis combined with the Euclidean Distance method is effective in monitoring shoreline changes over time. Overall, shoreline changes at Pulau Merah are significant and uneven, requiring focused management on areas with continuous erosion, while other areas should be monitored regularly and strengthened through coastal vegetation.